Jabberwocky [videorecording (Blu-Ray)] - Gilliam, Terry; Gilliam, Terry; Palin, Michael; Corbett, Harry H.; Le Mesurier, John, 1912-1983; Mitchell, Warren; Wall, Max, 1908-1990; Carroll, Lewis, 1832-1898 (The Criterion collection, 2017)
A young peasant, with no interest in adventure or fortune, is mistaken as the kingdom's only hope when a horrible monster threatens the countryside.